Successful Management of a Mycotic Pseudoaneurysm Involving an Arch Branch Using an Endovascular Stent Graft - Choi, Si Young; Kim, Chi Kyung; Park, Chan Beom (The Thoracic and Cardiovascular Surgeon, 2013)
Mycotic aneurysms in the aortic arch are extremely rare and represent a challenging surgical problem. Although surgery is the standard treatment, application of endovascular repair has been extended, but this technique carries a concern regarding the interposition of an artificial graft in the infected lesion. We present the case of an infected pseudoaneurysm in the thoracic aorta which was successfully excluded by treatment with a stent graft.
Keywords: mycotic aneurysm; endovascular; aortic arch